A Newly Discovered Late Antique Monastery and Islamic Town on Sīnīya Island, Umm al-Quwain. - Power, ````Timothy; Degli Esposti, Michele; Hoyland, Robert; Kannouma, Rania (Proceedings of the Seminar for Arabian Studies, 2023)
The Tourism and Archaeology Department of the Government of Umm al-Quwain (TAD-UAQ), in collaboration with its local and international research partners, has set up a new project on Sīnīya Island in the historic Khawr al-Bayḍāʾ lagoon. The project was prompted by development plans and informed by a preliminary survey that located significant archaeological remains. A comprehensive survey subsequently revealed the existence of dozens of smaller sites across the island, mostly consisting of pottery scatters, shell middens and cemeteries. Survey work was complemented by drone mapping, geomorphological investigations, and geophysical prospection. Two sites of outstanding cultural significance were selected for excavation, including a late antique monastery in the northeast of the island and an Islamic town in the southwest. This paper will provide and introduction to the Sīnīya Island Archaeological Project and present the preliminary results of the excavations.